FORMATIVE ASSESSMENT - Welly Ardiansyah; Murwani Ujihanti; Nurul Aryanti; Wasitoh Meirani (HOLISTICS, 2018)
The use of formative assessments, or other diagnostic efforts within classrooms, provides information that should help facilitate  improved pedagogical practices and instructional outcomes. However, a review of the formative assessment literature revealed that there is no agreed upon lexicon with regard to formative assessment and suspect methodological approaches in the efforts to demonstrate positive effects that could be attributed to formative assessments. Thus, the purpose of this article was to set out to clarify the terminology related to formative assessment and its usage.